Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Section 10.4 - Adding, Subtracting, and Multiplying Radical Expressions - Exercise Set: 53

Answer

$(2\sqrt{x}-5)(3\sqrt{x}+1)=6x-13\sqrt{x}-5$

Work Step by Step

$(2\sqrt{x}-5)(3\sqrt{x}+1)$ Evaluate the product and simplify if possible: $(2\sqrt{x}-5)(3\sqrt{x}+1)=(2\sqrt{x})(3\sqrt{x})+2\sqrt{x}-15\sqrt{x}-5=...$ $...=6\sqrt{x^{2}}+2\sqrt{x}-15\sqrt{x}-5=6x+2\sqrt{x}-15\sqrt{x}-5=...$ $...=6x-13\sqrt{x}-5$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.